The shaping of Israeli identity : myth, memory and trauma - Ṿisṭrits, Roberṭ 1945-2015 (Cass, 1995)
This volume contains essays which examine in an original provocative and critical perspective the fundamental myths, symbols and historical memories that have played an active role in shaping the development of Israeli society.